Implementation of Warm Compress on Mrs. A. R., a Malaria Patient with Hyperthermia, in Class I & II Ward of Serui General Hospital (Journal of Social And Education Research, 2025)
. Introduction Malaria is an infectious disease caused by Plasmodium through the bite of a female Anopheles mosquito. In 2022, WHO recorded 249 million cases of malaria globally. In Indonesia, cases reached 418,546 in 2023, with Papua contributing 92% of the total cases. Yapen Islands Regency recorded 21,238 cases in the first semester of 2023. One of the main symptoms of malaria is hyperthermia, which if not treated immediately, can cause serious complications such as febrile seizures, impaired consciousness, and organ damage. This therapy stimulates peripheral vasodilation, which helps reduce body temperature naturally. The purpose of this study was to describe the implementation and effectiveness of warm compress therapy in malaria patients with hyperthermia. The method used is a descriptive case study. This study uses a descriptive case study approach with the aim of describing the implementation of warm compress therapy as a nursing intervention in malaria patients with hyperthermia problems. The results showed a significant decrease in body temperature and increased patient comfort. The suggestion from this study is the need for education to families and health cadres about this therapy procedure. In conclusion, warm compress therapy is a simple, safe, effective nursing solution that is suitable for use in areas with limited resources. Hyperthermia treatment must be carried out quickly and precisely. An effective and practical solution is the application of warm compress therapy to certain areas of the body (forehead, armpits, groin) using water at a temperature of 37–40°C.